Comparison of Platelet Interaction with Subendothelium of Human Renal and Umbilical Arteries and the Extracellular Matrix Produced by Human Venous Endothelial Cells - Sakariassen, Kjell S; Banga, Jan Dirk; de Groot, Philip G; Sixma, Jan J (Thrombosis and Haemostasis, 1984)
Platelet interaction with subendothelium of human renal and umbilical arteries and with the extracellular matrix produced by cultured human venous endothelial cells was compared in flowing citrated blood by using an annular and a rectangular perfusion chamber.The renal arteries were post mortem specimens from adults showing, often pronounced, intimal fibrosis, whereas the umbilical arteries had well organized parallel arranged smooth muscle cells, without elastic membranes. The extracellular matrix obtained after removal of endothelial cells with Triton X-100 was homogenously attached to its substratum.Significantly more platelets adhered to the extracellular matrix than to the subendothelia. This discrepancy was most pronounced in reconstituted blood with plasma from a patient with homozygous severe von Willebrand’s disease (subtype III). No differences in platelet adherence and platelet aggregate formation were noted between the subendothelia. Platelet aggregate formation was poor on all surfaces.These data indicate that the extracellular matrix produced by endothelial cells is at least as reactive for the interaction with platelets as subendothelium, probably partly synthesized by smooth muscle cells.
Keywords: Platelet adherence; Subendothelium and extracellular matrix